Kemampuan Pemecahan Masalah Matematika Ditinjau dari Tingkat Kecemasan Matematika (Math Anxiety) - Adhienda Maulidyah Rachmah; Ika Kurniasari (MATHEdunesa, 2026)
Math problem solving ability is the achievement of a person to carry out a series of processes in solving math problems, namely understanding the problem, developing a solution plan, implementing a solution plan, and checking back. This research is descriptive qualitative research that aims to describe the math problem solving ability of junior high school students in terms of the level of math anxiety. The research subjects consisted of one learner per high, medium, and low math anxiety level. The data collection techniques used were questionnaires, tests and interviews. Data were anaplan anded on the stages of problem solving: understand the problem, devising a plan, carrying out the plan and looking back. The results of the study showed differences in students' mathematical problem-solving abilities based on their level of mathematical anxiety. Students with high mathematical anxiety used inappropriate strategies and produced incorrect answers and were not confident in checking. Students with moderate mathematical anxiety used strategy manuals and produced correct answers but were less precise in the application concept and were not confident in checking. Students with low mathematical anxiety used appropriate strategies, applied concepts correctly, performed calculations correctly, and were confident in checking.